Recombinant adeno‐associated viral (rAAV) vectors mediate efficient gene transduction in cultured neonatal and adult microglia. (20th March 2015) - Su, Wei; Kang, John; Sopher, Bryce; Gillespie, James; Aloi, Macarena S.; Odom, Guy L.; Hopkins, Stephanie; Case, Amanda; Wang, David B.; Chamberlain, Jeffrey S.; Garden, Gwenn A.
Abstract: Microglia are a specialized population of myeloid cells that mediate CNS innate immune responses. Efforts to identify the cellular and molecular mechanisms that regulate microglia behaviors have been hampered by the lack of effective tools for manipulating gene expression. Cultured microglia are refractory to most chemical and electrical transfection methods, yielding little or no gene delivery and causing toxicity and/or inflammatory activation. Recombinant adeno‐associated viral (rAAVs) vectors are non‐enveloped, single‐stranded DNA vectors commonly used to transduce many primary cell types and tissues. In this study, we evaluated the feasibility and efficiency of utilizing rAAV serotype 2 (rAAV2) to modulate gene expression in cultured microglia. rAAV2 yields high transduction and causes minimal toxicity or inflammatory response in both neonatal and adult microglia. To demonstrate that rAAV transduction can induce functional protein expression, we used rAAV2 expressing Cre recombinase to successfully excise a LoxP‐flanked miR155 gene in cultured microglia. We further evaluated rAAV serotypes 5, 6, 8, and 9, and observed that all efficiently transduced cultured microglia to varying degrees of success and caused little or no alteration in inflammatory gene expression. These results provide strong encouragement for the application of rAAV‐mediated gene expression in microglia for mechanistic and therapeutic purposes. Neonatal microglia are functionally distinct from adult microglia, although the majority of in vitro studies utilize rodent neonatal microglia cultures because of difficulties of culturing adult cells. In addition, cultured microglia are refractory to most methods for modifying gene expression. Here, we developed a novel protocol for culturing adult microglia and evaluated the feasibility and efficiency of utilizing Recombinant Adeno‐Associated Virus (rAAV) to modulate gene expression in cultured microglia. Abstract : Neonatal microglia are functionally distinct from adult microglia, although the majority of in vitro studies utilize rodent neonatal microglia cultures because of difficulties of culturing adult cells. In addition, cultured microglia are refractory to most methods for modifying gene expression. Here, we developed a novel protocol for culturing adult microglia and evaluated the feasibility and efficiency of utilizing Recombinant Adeno‐Associated Virus (rAAV) to modulate gene expression in cultured microglia. This article is part of the Special Issue "Neuroinflammation – A Two Way Street Directing CNS Injury and Repair".